2019
DOI: 10.3389/fneur.2019.00361
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Management of Trochleodynia, Trochleitis, and Trochlear Headache

Abstract: Migraine and tension-type headaches (TTHs) comprise a significant burden of neurological disease globally. Trochleodynia, also known as primary trochlear headache or trochleitis, may go unrecognized and contribute to worsening of these headache disorders. It may also present in isolation. We review the English literature on this under-recognized condition and describe what is known about the theorized pathophysiology, clinical presentation, and differential diagnosis. We also present a management algorithm for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 56 publications
0
23
1
1
Order By: Relevance
“…Similar to our study, previous studies have also reported a variable (10-60%) prevalence of prior history of headaches in patients with CTRH. 6,7 In our CTRH group, binocular diplopia was reported by nearly 50% patients, local swelling was noted only with trochleitis and MRI orbit abnormalities only with ST. These findings are similar to the study conducted by Smith et al 7 Refractoriness to prophylaxis was found to be associated with acute-subacute onset, TTH-like headaches, local swelling, and presence of autoantibodies.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Similar to our study, previous studies have also reported a variable (10-60%) prevalence of prior history of headaches in patients with CTRH. 6,7 In our CTRH group, binocular diplopia was reported by nearly 50% patients, local swelling was noted only with trochleitis and MRI orbit abnormalities only with ST. These findings are similar to the study conducted by Smith et al 7 Refractoriness to prophylaxis was found to be associated with acute-subacute onset, TTH-like headaches, local swelling, and presence of autoantibodies.…”
Section: Discussionmentioning
confidence: 63%
“…A likely explanation for this observation is that most of these studies included only severe cases requiring local injections. 2,6,7 Local injections were found necessary in less than half of our refractory patients.…”
Section: Discussionmentioning
confidence: 85%
“…All of these headaches are linked to V1, but little is known about their molecular pathophysiology. This is also the case for trochleodynia which is a spectrum of disorders characterized by pain arising from the trochlear region [122] and idiopathic ophthalmodynia [123] which is linked to pain in the eyeball.…”
Section: Other Painful Conditionals Of the Trigeminal Nerve Branchesmentioning
confidence: 95%
“…Some patients may report deep seated pain retro-orbitally with down radiation to the neck [32]. Localized trochlea pain/tenderness as pointed by a patient which is aggravated by stress physically or emotionally or contraction of superior oblique (SO) muscle and headache on the front side from the superior nasal orbit extending periorbitally to ipsilateral boundaries is useful to distinguish clinically trochleodynia from THS, therefore in the deficit of a CN palsy neuroimaging is not recommend for trochleodynia exclusion [33].…”
Section: Presenting History/symptomsmentioning
confidence: 99%